2018
DOI: 10.1080/08897077.2017.1365803
|View full text |Cite
|
Sign up to set email alerts
|

Interprofessional Prescription Opioid Abuse Communication among Prescribers and Pharmacists: A Qualitative Analysis

Abstract: Background Prescribers and community pharmacists commonly perceive prescription opioid abuse to be a problem in their practice settings and communities. Both cohorts have expressed support for interventions that improve interprofessional communication and reduce prescription opioid abuse. The objective of this study was to describe prescription opioid abuse-related communication among and between prescribers and community pharmacists in South Central Appalachia. Methods The investigators conducted five focus g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…The best way to ensure precise, secure, and confidential care is for pharmacists to have real-time access to all health information related to the patients’ SUD and co- morbidities. 129 , 130 All pharmacists and pharmacy students should receive training to reduce or eliminate stigma in their practices to ensure all patients receive compassionate, patient-centered care from all members of the care team. 77 , 79 , 131 - 137…”
Section: Vision For the Futurementioning
confidence: 99%
See 1 more Smart Citation
“…The best way to ensure precise, secure, and confidential care is for pharmacists to have real-time access to all health information related to the patients’ SUD and co- morbidities. 129 , 130 All pharmacists and pharmacy students should receive training to reduce or eliminate stigma in their practices to ensure all patients receive compassionate, patient-centered care from all members of the care team. 77 , 79 , 131 - 137…”
Section: Vision For the Futurementioning
confidence: 99%
“…The best way to ensure precise, secure, and confidential care is for pharmacists to have real-time access to all health information related to the patients' SUD and co-morbidities. 129,130 All pharmacists and pharmacy students should receive training to reduce or eliminate stigma in their practices to ensure all patients receive compassionate, patient-centered care from all members of the care team. 77,79,[131][132][133][134][135][136][137] Every student pharmacist should participate in an interprofessional expanded SUD curriculum integrated throughout didactic classes such as toxicology, pharmacology, pharmacotherapeutics, as well as introductory and advanced pharmacy practice experiences.…”
Section: Critical Issues Obstacles and Challengesmentioning
confidence: 99%
“… 27 Qualitative research has identified some key factors influencing implementation of PDMPs such as linkage to electronic health records (EHR), 29 - 31 and communication barriers between physicians and pharmacists. 32 , 33 In addition, qualitative research has illuminated the perceived unintended consequences of the PDMP by PDMP staff, law enforcement officials, and administrative agency employees. 17 However, these studies have not focused on how implementation factors such as monitoring and enforcement vary by state or how these differences may influence the perceived unintended consequences of the PDMP.…”
Section: Introductionmentioning
confidence: 99%
“…Descriptive research has shown that lack of confidence, lack of time, unwillingness to communicate with prescribers, limited familiarity with screening materials, and inability to identify patients at risk of overdose all limit pharmacist engagement with patients at risk for substance misuse. [13][14][15] Despite perceived barriers , at the point of dispensing prescription opioid analgesics (POA) and MOUD, community pharmacists are well positioned to engage patients in conversations that span all three levels of OUD prevention, and seek to optimize patient care.…”
Section: Introductionmentioning
confidence: 99%